ETIKA RELIGIUS DALAM TEKS LONTAR SILAKRAMANING AGURON-GURON: SEBUAH ANALISIS POLA INTERAKSI GURU-SISWA - Jro Ayu Ningrat (Widya Sandhi, 2021)
This study focuses on the study of religious ethics in the lontar text of Sila Kramaning Aguron-guron in building a pattern of interaction between teachers and students (sisya) according to Hindu teachings. The method used is an interpretive qualitative method using a content analysis pattern. This study focuses on the description of the teachings of religious ethics contained in the lontar Sila Kramaning Aguron-guron on sheet 1b and analyzes the aspects of the teachings related to building patterns of interaction between teachers and students (sisya). This study formulated three results in accordance with those formulated in the research focus. First, the description of the lontar is more focused on the aspect of religious ethics that must be adhered to and obeyed by the student (sisya) in improving spiritual quality in order to achieve the goal of life in accordance with what is taught in the teachings of Hinduism. Second, the essential values ​​contained in the lontar Sila Kramaning Aguron-guron are related to building patterns of interaction between teachers and students in everyday life. In essence, the teachings taught in the lontar text must be used as guidelines by Hindus who want to improve the quality of spiritual life in achieving eternal freedom.